Качественные свойства решений задачи Неймана для квазилинейного параболического уравнения высокого порядка - Тадеев, А.Ф. (Український математичний журнал, 1993)
The property of localization of perturbations is proved for a solution of an initial boundary-value Neumann problem in a region D=Ωx, t>0, where Ω is a region in Rⁿ with a noncompact boundary.